Lanthanide(iii) complexes of monophosphinate/monophosphonate DOTA-analogues: effects of the substituents on the formation rate and radiolabelling yield - Procházková, Soňa; Kubíček, Vojtěch; Kotek, Jan; Vágner, Adrienn; Notni, Johannes; Hermann, Petr (Dalton transactions (Cambridge, England, 2018)
H4dota and its analogues are routinely used for complexation of lanthanide radioisotopes in nuclear medicine. Many of the radioisotopes have short half-lives and, thus, the complexation rate plays an important role. Notwithstanding that, the relationship between ligand structures and complexation rates is not well understood. Here we report a complexation study of H4dota and its analogues bearing one phosphonate or phosphinate pendant arm. The substituents on the phosphinate group were non-coordinating (-H) or contained another coordinating group (-CH2N(CH2COOH)2, -CH2PO2H2 or -CH2NH2). The basicity of ligands, stability of reaction intermediates, formation rates of CeIII complexes, and 177LuIII radiolabelling were studied. The complexation rates and labelling yields do not show any correlation with ligand basicity. In contrast, the additional chelating group attached to the pendant arm plays an important role. A decreased complexation rate and lower labelling yield were found for compounds bearing an additional amino group, whereas improved properties were found for the compound bearing a geminal bis(phosphinate) pendant arm. It indicates that the introduction of chelating pendant arms with acidic coordinating groups might be a promising strategy to improve radiolabelling of macrocyclic carriers with metal radioisotopes.